Применение импульсного электрического разряда для очистки воды от нефтепродуктов; Известия вузов. Физика; Т. 56, № 7-2 - Корнев Я. И. Яков Иванович; Сапрыкин Ф. Е. Филипп Евгеньевич; Прейс К. А. Константин Андреевич; Хаскельберг М. Б. Михаил Борисович; Грязнова Е. Н. Елена Николаевна; Шиян Л. Н. Людмила Николаевна; Хряпов П. А. Петр Александрович; Галанов А. И. Андрей Иванович (2013, 2013)
Заглавие с экрана